2013
DOI: 10.1016/j.jcv.2013.06.008
|View full text |Cite
|
Sign up to set email alerts
|

An artesunate-containing antimalarial treatment regimen did not suppress cytomegalovirus viremia

Abstract: Background Additional drugs are needed for the treatment of cytomegalovirus (CMV) infection. Artesunate is an antimalarial drug that has activity against CMV in vitro and in a rodent model. Only a small number of case reports are available describing the clinical effects of artesunate on CMV infection, and these yielded inconsistent results. Objective To evaluate the effect of artesunate on CMV infection, using blood samples collected from children who participated in malaria treatment trials. Study design… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…One of these combinations, AS plus amodiaquine (AQ), was tested against HCMV in a clinical study conducted on 494 Ugandan children treated for acute malaria either with the ACT or with sulfadoxine-pyrimethamine plus AQ. No measurable difference was observed in either the HCMV detection frequency or load in the blood of children in the two groups [49].…”
Section: Artesunate and Hcmvmentioning
confidence: 78%
“…One of these combinations, AS plus amodiaquine (AQ), was tested against HCMV in a clinical study conducted on 494 Ugandan children treated for acute malaria either with the ACT or with sulfadoxine-pyrimethamine plus AQ. No measurable difference was observed in either the HCMV detection frequency or load in the blood of children in the two groups [49].…”
Section: Artesunate and Hcmvmentioning
confidence: 78%
“…A modestly reduced cervical CMV shedding was observed. Finally, the effect of artesunate on CMV was investigated in Uganda, as some case reports had described activity against CMV. Yet a 3‐day artesunate containing antimalarial regimen had no detectable effect on CMV viremia in children with malaria.…”
Section: Resultsmentioning
confidence: 99%
“…al did not observe a difference in their 3-day follow up study in which dried blood spots were used to evaluate viremia in patients receiving artemisinin combination therapy (ACTs) for malaria (17). Since viremia is likely uncommon in the normal host and typically at low levels, (only 11% of participants in that study were found to have low level viremia) changes in viral loads during artemisinin therapy may have been difficult to detect (25).…”
Section: Discussionmentioning
confidence: 99%
“…While there is compelling in vitro data that these compounds are highly effective against CMV, in vivo data supporting the use of artemisinin derivatives is scattered and consists largely of case reports and one observational clinical study (15, 16). A trial of Ugandan children receiving either artesunate plus amodiaquine or sulfadoxine-pyrimethamine plus amodiaquine showed no difference in CMV viral loads measured from dried blood spots at day one or day three following therapy (17). …”
Section: Introductionmentioning
confidence: 99%